Open letter to the incoming director general of the World Health Organization: time to refocus. Issue 7576 (9th November 2006) - Levine, Ruth
Abstract : Ruth Levine argues that WHO needs to concentrate on confronting global health risks, improving the health of poor people, and marshalling technical expertise